Automatic FLR identification and density estimation from SuperDARN VLOS data to identify magnetospheric regions - Hideaki, Kawano; Yukimatu, Akira Sessai; Nishitani, Nozomu; Tanaka, Yoshimasa; Saita, Satoko; Hori, Tomoaki; Lester, Mark (2019)
The Tenth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper atmospheric sciences, Wed. 4 Dec. /Entrance Hall (1st floor) at National Institute of Polar Research (NIPR) conference object